If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + (-12) = 60 6m + -12 = 60 Reorder the terms: -12 + 6m = 60 Solving -12 + 6m = 60 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6m = 60 + 12 Combine like terms: -12 + 12 = 0 0 + 6m = 60 + 12 6m = 60 + 12 Combine like terms: 60 + 12 = 72 6m = 72 Divide each side by '6'. m = 12 Simplifying m = 12
| 0.3(x+9)+5=67 | | 0.3(x+9)+=67 | | 45=10+x*5/2 | | -3x+3=-24 | | 2x+10y=-16 | | 18z^7-15z^4/3z^3 | | 9+5x=-36 | | -4x-10=-14 | | -10+4x=10 | | (4x)(x+5)=0 | | 1x^2-x-1=0 | | 8x-6=25 | | 4x-22=4x-22 | | y=-7(-13) | | 5.5+r^2=36+r^2 | | 6t=3(n+4)-t | | 3-4x=-3-x^2+4x | | 1/2(5x+2)=4 | | 3y=-12+15x | | 4h-8=3h+21 | | 5.5+2r=36+r^2 | | 3/4(x+8)=-2 | | -2x-3=-23 | | -1/4(X-8)+1/2(X+2) | | 10x^2=9x+7 | | -1.25+x+3= | | 5x-x-5=-37 | | -(4y+3)-(-3y-8)=3 | | 0+2y=3 | | -3x-4=3X+10 | | 0=7x-3 | | 625+x^2=0 |